Validitas Pengembangan Media Pembelajaran Kartu Kuartet Berbasis Pictorial Riddle Materi Penerapan Sila-sila Pancasila Siswa Kelas III SDN Mrican 1 - Fatimah, Dwi Rahmawati; Wiguna, Frans Aditia; Saidah, Karimatus (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study was motivated by the limited use of instructional media for the Pancasila Education subject in Grade III at SDN Mrican 1, which resulted in low student engagement during the learning process. Furthermore, the topic regarding the application of Pancasila principles was considered difficult for students to grasp, creating a need for instructional media. The objective of this study was to determine the validity of "quartet" card media based on the "pictorial riddle" approach, specifically for the topic of applying Pancasila principles. The study employed the Research and Development (R&D) method using the ADDIE model, which comprises the stages of analysis, design, development, implementation, and evaluation. However, the scope of this study was limited to the development stage, as the primary goal was to produce valid media through an expert validation process. Data were collected using validation sheets administered to subject matter experts and media experts. The results indicated that the validation score from the subject matter expert reached 94%, classifying it as "highly valid." Similarly, the validation score from the media expert was 88%, also falling into the "highly valid" category. The average validation score from both experts was 91%, placing it in the "highly valid" category. Based on these results, the quartet card instructional media featuring pictorial riddles and covering the application of Pancasila principles met the criteria for high validity and demonstrated potential for use as a learning support tool.